Two correct answers:
9 + x
x + 9
Or you can say
x - -9
or
9 - -x
First of all what answers are there
Y = 2 ( X - 3 ) ^ 2 - 4 =-4
Answer:
D.) 8
Step-by-step explanation:
You can use the Pythagorean theorem because this is a right triangle:
![a^2+b^2=c^2](https://tex.z-dn.net/?f=a%5E2%2Bb%5E2%3Dc%5E2)
a and b are the legs and c is the hypotenuse. The hypotenuse is always the longest side in a right triangle (since it is opposite the biggest angle). The two legs squared have to add up to the hypotenuse squared.
Fill in values:
![a^2+15^2=17^2](https://tex.z-dn.net/?f=a%5E2%2B15%5E2%3D17%5E2)
Simplify exponents:
![a^2+225=289](https://tex.z-dn.net/?f=a%5E2%2B225%3D289)
Isolate the variable. Subtract 225 from both sides:
![a^2+225-225=289-225\\a^2=64](https://tex.z-dn.net/?f=a%5E2%2B225-225%3D289-225%5C%5Ca%5E2%3D64)
Find the square root of both sides:
![\sqrt{a^2}=\sqrt{64}\\ a=8](https://tex.z-dn.net/?f=%5Csqrt%7Ba%5E2%7D%3D%5Csqrt%7B64%7D%5C%5C%20%20a%3D8)
The missing leg length is 8.
F5=(256)f1=16 hope this helps